Health Monitoring of an Existing RC Structure Considering Seismic Analysis Using Analysis Tools Staad - Abhishek Sharma; Pradeep Kumar Nirmal; Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2021)
Seismic retrofitting is mainly done to meet the seismic safety requirements. The planning of alterations to existing buildings differs from new planning through an important condition; the existing construction must be taken as the basis of all planning and building actions. India is one of the most earthquake prone countries in the world and has experienced several major or moderate earthquakes during the last 15 years. About 50-60 % of the total area of the country is vulnerable to seismic activity of varying intensities. Many existing buildings do not meet the seismic strength requirement. In this study we are performing health monitoring on existing old structure G+2, using rebound hammer to evaluate its present strength and analyze the structure using analysis tool staad.pro. In this study we are performing time history analysis (el-centrino) with retrofitting over weak members.
Keywords: Time History; Staad.pro; Non Destructive Test; Rebound Hammer; Existing Structure; Retrofitting; Analysis